Pengaruh Model Problem Based Learning (PBL) Berbantuan LKPD terhadap Hasil Belajar Siswa: The Effect of Problem-Based Learning (PBL) Model Assisted by Student Worksheets (LKPD) on Students' Learning Outcomes - Alafiah, Sajinatullaili; Syahidi, Khaerus; Zahara, Laxmi; Yusri, Ahmad (Literasi: Jurnal Pendidikan Guru Indonesia, 2025)
This study aims to determine whether or not there is an effect of the PBL (Problem Based Learning) model assisted by Student Worksheets (LKPD) on student learning outcomes in the elasticity material at MA Mu'allimat NWDI Pancor for the 2022/2023 academic year ".This study uses an experimental method with a Posttest-Only Control Design, which only provides a post-test at the end of the treatment. The population in this study were all students of class XI IPA MA Mu'allimat NWDI Pancor. Meanwhile, the samples in this study were class XI IPA 1 as the experimental group and class XI IPA 3 as the control group. The two samples were randomly selected using the Cluster Random Sampling (Area Sampling) technique. The experimental group was taught physics using the PBL (Problem Based Learning) model with the help of Student Worksheets (LKPD) and the control group was taught physics using the conventional model.The research data were analyzed using two-party t-test. Based on the research results obtained 〖 t〗_hitung (4,513)>t_tabel (1,998) at a significant level of 0.05. Because〖 t〗_hitung>t_tabel, then H0 is rejected and Ha is accepted. Thus,it can be concluded that there is an effect of the PBL (Problem Based Learning) model assisted by Student Worksheets on student learning material at MA Mu’allimat NWDI Pancor in the 2022/2023 academic year.